A hybrid quantum particle swarm optimization for the Multidimensional Knapsack Problem. (October 2016) - Haddar, Boukthir; Khemakhem, Mahdi; Hanafi, Saïd; Wilbaut, Christophe
Abstract: In this paper we propose a new hybrid heuristic approach that combines the Quantum Particle Swarm Optimization technique with a local search method to solve the Multidimensional Knapsack Problem. The approach also incorporates a heuristic repair operator that uses problem-specific knowledge instead of the penalty function technique commonly used for constrained problems. Experimental results obtained on a wide set of benchmark problems clearly demonstrate the competitiveness of the proposed method compared to the state-of-the-art heuristic methods.